Teaming up : making the transition to a self-directed, team-based organization - Ray, Darrel; Bronstein, Howard (New York : McGraw-Hill, 1995)
Plenty of books will tell you why self-directed teams are good for businesses and the people in them. But very few also show how to set teamwork into motion, day by day and year by year. If you're seeking that "second-generation" level of guidance - how-to, detailed, based on struggles and successes at organizations just like yours - look no further than Teaming Up. Dr. Darrel Ray has front-line experience in helping teams grow at manufacturing and service companies, government and social service agencies, Fortune 500 giants, and small firms. His approach has been proven to work in union and non-union environments, and the payoffs have been measurable: higher morale, better use of resources, and dramatic positive impact on bottomline profit.
Pt. 1. Preparing for Self-Directed Work Teams. 1. Why Self-Directed Teams! 2. The Concept of Self-Management. 3. Top Management and Self-Direction. 4. New Ways to Work -- Pt. 2. Designing for Self-Direction. 5. The Steering Committee. 6. Assessing the Organization. 7. Redesigning Work and the Team Concept. 8. The Role of the Team Developer. 9. Understanding Group Process -- Pt. 3. A System for Self-Directed Work Teams. 10. Organizing the Self-Directed Work Team. 11. Training the Self-Directed Work Team. 12. Modeling and Communication. 13. Teaching Teams to Communicate. 14. Hazards of Teams -- 15. Epilogue: The Future of Teams.
Includes bibliographical references (p. 241-244) and index.
Keywords: Self-directed work teams